2019
DOI: 10.3324/haematol.2019.229450
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of heme iron is associated with ferritin and hemoglobin levels in Dutch blood donors: results from Donor InSight

Abstract: Whole blood donors, especially frequently donating donors, have a risk of iron deficiency and low hemoglobin levels, which may affect their health and eligibility to donate. Lifestyle behaviors, such as dietary iron intake and physical activity, may influence iron stores and thereby hemoglobin levels. We aimed to investigate whether dietary iron intake and questionnaire-based moderate-to-vigorous physical activity were associated with hemoglobin levels, and whether ferritin levels mediated these associations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 44 publications
1
15
1
Order By: Relevance
“…The increase in serum ferritin concentration was established to be consistent with the increase of Hb levels. Similar observations were also reported by other researchers [27].…”
Section: Discussion/conclusionsupporting
confidence: 93%
See 1 more Smart Citation
“…The increase in serum ferritin concentration was established to be consistent with the increase of Hb levels. Similar observations were also reported by other researchers [27].…”
Section: Discussion/conclusionsupporting
confidence: 93%
“…Threshold values are not specified as well [26]. The iron balance is also affected by the hormonal background, as not only progesterone increases during pregnancy but also estrogen, which affects iron metabolism [27].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Consequently, heme iron can contribute to over 40% of the total absorbed iron in diet (33,34) . Heme iron intake has been previously shown a positive association with body iron store, while nonheme iron intake has been previously shown no association (35)(36)(37) .…”
Section: Discussionmentioning
confidence: 98%
“…In healthy individuals, the amount of iron in the body is controlled by its absorption, mobilization, storage, and recycling, but iron excretion is not actively regulated (45) . Dietary iron intake might increase iron absorbed by the intestine and body iron stores (46) , studies have previously reported a positive association between dietary iron intake and body iron status (35,38) . Iron could trigger inflammatory responses and promote ROS generation (47,48) .…”
Section: Discussionmentioning
confidence: 99%
“…Higher body mass index (BMI) is associated with higher ferritin levels 8 . In recent decades, many other factors that affect iron status have been identified: diet, 9,10 genetics, 11,12 ethnicity, 13 and iron supplementation, which is mostly studied among blood donors 14,15 …”
Section: Introductionmentioning
confidence: 99%